Berberine hydrochloride inhibits inflammatory response via regulating the miRNA-140-5p/TLR4/NF-κB signaling pathway in oral lichen planus - Qiong Zhang; Liangjun Zhong; Xing Chen; Jintao Wang (Bangladesh Pharmacological Society, 2020)
The present study investigates the anti-inflammatory mechanism of berberine hydrochloride in the oral lichen planus. The local inflammatory environment of the oral lichen planus was mimicked, through which lipopolysaccharides stimulated keratinocyte HaCaT cells. Berberine hydrochloride suppressed the activation of the TLR4/NF-κB inflammatory signaling pathway by up-regulating miRNA-140-5p, which is an independent risk factor for the oral lichen planus. Furthermore, miRNA-140-5p inhibited the TLR4/NF-κB inflammatory signaling pathway by directly suppressing TLR4 expression. Therefore, the present study suggests that berberine hydrochloride inhibits the inflammatory response by up-regulating miRNA-140-5p to suppress the activation of the TLR4/NF-κB inflammatory signaling pathway in the oral lichen planus.